2014
DOI: 10.1186/1756-3305-7-110
|View full text |Cite
|
Sign up to set email alerts
|

Management of canine leishmaniosis in endemic SW European regions: a questionnaire-based multinational survey

Abstract: BackgroundCanine leishmaniosis (CanL) caused by Leishmania infantum is a widespread endemic disease in SW Europe. This study was designed to determine how veterinarians clinically manage CanL in this region by analysing information collected in a questionnaire completed by local veterinarians working in clinics in France, Portugal, Greece, Spain, Italy and Slovenia.MethodsOver the period 2004–2011, a questionnaire on CanL was sent to 12,546 small animal clinics located in the six countries surveyed. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 79 publications
6
44
0
1
Order By: Relevance
“…They have been used in studies at regional (Gálvez and others 2011, Alcover and others 2013, Ballart and others 2013), national (Oliveira and others 2010) and multinational levels (Bourdeau and others 2014, Mattin and others 2014). The classical questions used in the EDEN project were extended in the present work to cover the use of new immunomodulating preventive methods in clinical practice, including questions on the use of domperidone and the use and safety of vaccination (CaniLeish).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been used in studies at regional (Gálvez and others 2011, Alcover and others 2013, Ballart and others 2013), national (Oliveira and others 2010) and multinational levels (Bourdeau and others 2014, Mattin and others 2014). The classical questions used in the EDEN project were extended in the present work to cover the use of new immunomodulating preventive methods in clinical practice, including questions on the use of domperidone and the use and safety of vaccination (CaniLeish).…”
Section: Discussionmentioning
confidence: 99%
“…Given the novelty of these tools, the results of the present study are important because they provide preliminary data about their use, efficacy and safety. Two studies have previously collected information regarding the opinion of veterinarians about vaccine recommendation (Oliveira and others 2010, Bourdeau and others 2014) and one about vaccine use in France, the country where it was first available (mean 0.31 per cent of dogs receiving the vaccine per department) (Mattin and others 2014). …”
Section: Discussionmentioning
confidence: 99%
“…of Pages 7 (IFAT, ELISA) and molecular (conventional, nested and real time PCR) procedures are used individually or in combination (Baneth and Aroch, 2008). IFAT is today one of the most commonly used methods for detecting anti-L. infantum antibodies (Solano-Gallego et al, 2009;Bourdeau et al, 2014) due to its high sensitivity and specificity (Mancianti et al, 1995). However, epidemiological studies in endemic areas of CanL has shown higher prevalence of infection by means of molecular techniques than seroprevalence (Baneth and Aroch, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Generally, IFAT, ELISA and the rapid in-house kits are the most commonly employed methods (Bourdeau and others 2014). The IFAT is considered the reference method for anti- Leishmania serology in dogs (Gradoni and Gramiccia 2008, EFSA AHAW Panel 2015) based on its high sensitivity and specificity (near 100 per cent for both) except in areas endemic for Trypanosoma cruzi where it may give false positive results.…”
Section: Diagnosismentioning
confidence: 99%
“…Lowest sensitivity is associated with infected dogs without clinical signs, while highest sensitivity is seen for dogs with overt disease. Various in-house serological tests are commercially available and are particularly attractive to practising veterinarians because they give immediate results (Bourdeau and others 2014). However, their major disadvantage is that they are qualitative and thus any positive result needs to be followed by a quantitative test.…”
Section: Diagnosismentioning
confidence: 99%